Specific Activation of an I-Like Element in Drosophila Interspecific Hybrids - Carnelossi, Elias A. G. [UNESP]; Lerat, Emmanuelle; Henri, Helene; Martinez, Sonia; Carareto, Claudia M. A. [UNESP]; Vieira, Cristina (Oxford Univ Press, 2014)
The non-long terminal repeat (LTR) retrotransposon I, which belongs to the I superfamily of non-LTR retrotransposons, is well known in Drosophila because it transposes at a high frequency in the female germline cells in I-R hybrid dysgenic crosses of Drosophila melanogaster. Here, we report the occurrence and the upregulation of an I-like element in the hybrids of two sister species belonging to the repleta group of the genus Drosophila, D. mojavensis, and D. arizonae. These two species display variable degrees of pre- and postzygotic isolation, depending on the geographic origin of the strains. We took advantage of these features to explore the transposable element (TE) dynamics in interspecific crosses. We fully characterized the copies of this TE family in the D. mojavensis genome and identified at least one complete copy. We showed that this element is transcriptionally active in the ovaries and testes of both species and in their hybrids. Moreover, we showed that this element is upregulated in hybrid males, which could be associated with the male-sterile phenotype.
Keywords: hybrids; non-LTR retrotransposon; repleta group; phylogeny